Adenosine A2A Receptor Mediates Inhibition of Synovitis and Osteoclastogenesis after Electroacupuncture in Rats with Collagen-Induced Arthritis. (6th March 2019) - Du, Zhong-heng; Zhang, Chun-wu; Xie, Wen-xia; Chen, Yong; Cong, Wen-jie; Wang, Ze-dong; Wang, En-pei; Wu, Guang-yu; Ye, Tian-shen
Abstract : Background . This study was to investigate the role of adenosine A2A receptors (A2AR) in inhibiting the effect of electroacupuncture (EA) on osteoclastogenesis in collagen-induced arthritis (CIA). Methods . Wistar rats were divided into four groups: sham-control group, CIA-control group, CIA-EA group, and CIA-EA-SCH58261 (A2AR antagonist) group. We detected tumor necrosis factor- α (TNF- α ), nuclear transcription factor- κ B (NF- κ B), receptor activator of NF- κ B ligand (RANKL), protein kinase A (PKA), and extracellular regulatory protein kinase 1/2 (ERK1/2) in peripheral blood by ELISA. PKA, ERK1/2, and NF- κ B in ankle joints were determined by western blotting. We evaluated the arthritis damage by histological examination and determined the number of osteoclasts by tartrate-resistant acid phosphatase (TRAP) staining. Results . EA treatment downregulated the expression of TNF- α, RANKL, PKA, ERK1/2, and NF- κ B in peripheral blood but increased the levels of PKA and ERK1/2 in ankle joints. Importantly, EA treatment reduced bone erosion as evidenced by the histological findings and inhibited osteoclastogenesis as revealed by TRAP staining. All these effects of the EA treatment were reversed by combining EA treatment with the A2AR antagonist SCH58261. Conclusion . Our data suggest that EA treatment activated A2AR. The effects of the A2AR antagonist SCH58261 suggest that the inhibition of osteoclast formation, the inhibition of TNF- α, RANKL, and NF- κ B expression, and the increase of ERK1/2 are all dependent on this EA-induced A2AR activation. It is therefore likely that these pathways with clearly defined roles in inflammation and bone erosion are at least partially involved in the mediation of the inhibition of synovitis and osteoclast formation induced by EA.